Improved Performance of Klaten District Education Office Employees In 2021 - Apriliani, Dyan; Istiatin, Istiatin; Sudarwati, Sudarwati (Economics and Business Solutions Journal, 2022)
This study aims to determine the effect of the variables of professionalism, placement, experience and work discipline on the performance of the employees of the Klaten Regency Education Office. This research method uses a quantitative research design. The population in all employees who work in the Klaten Regency Education Office is 86 people. The sampling technique used in this study is the Census technique with a sample of 86 respondents. Collecting data by using a questionnaire. The data analysis technique used was statistical analysis, namely multiple linear regression test, F test, t test, and coefficient of determination.The results showed that professionalism, placement, experience and work discipline had an effect on employee performance at the Klaten Regency Education Office.Suggestions from this research, the Education Office of Klaten Regency continues to improve professionalism, placement, experience and work discipline, so that employee performance will increase and be better than before.
Keywords: Employee Performance; Professionalism; Placement; Experience; Work Discipline